Genome-Wide Association Studies of Grain Yield Components in Diverse Sorghum Germplasm - Boyles, R. E.; Cooper, E. A.; Myers, M. T.; Brenton, Z.; Rauh, B. L.; Morris, Geoffrey P.; Kresovich, S. (My University, 2016)
Grain yield and its primary determinants, grain number and weight, are important traits in cereal crops that have been well studied; however, the genetic basis of and interactions between these traits remain poorly understood. Characterization of grain yield per primary panicle (YPP), grain number per primary panicle (GNP), and 1000-grain weight (TGW) in sorghum [Sorghum bicolor (L.) Moench], a hardy C-4 cereal with a genome size of similar to 730 Mb, was implemented in a diversity panel containing 390 accessions. These accessions were genotyped to obtain 268,830 single-nucleotide polymorphisms (SNPs). Genome-wide association studies (GWAS) were performed to identify loci associated with each grain yield component and understand the genetic interactions between these traits. Genome-wide association studies identified associations across the genome with YPP, GNP, and TGW that were located within previously mapped sorghum QTL for panicle weight, grain yield, and seed size, respectively. There were no significant associations between GNP and TGW that were within 100 kb, much greater than the average linkage disequilibrium (LD) in sorghum. The identification of nonoverlapping loci for grain number and weight suggests these traits may be manipulated independently to increase the grain yield of sorghum. Following GWAS, genomic regions surrounding each associated SNP were mined for candidate genes. Previously published expression data indicated several TGW candidate genes, including an ethylene receptor homolog, were primarily expressed within developing seed tissues to support GWAS. Furthermore, maize (Zea mays L.) homologs of identified TGW candidates were differentially expressed within the seed between small- and large-kernel lines from a segregating maize population.
Citation: Boyles, R. E., Cooper, E. A., Myers, M. T., Brenton, Z., Rauh, B. L., Morris, G. P., & Kresovich, S. (2016). Genome-Wide Association Studies of Grain Yield Components in Diverse Sorghum Germplasm. Plant Genome, 9(2), 17. doi:10.3835/plantgenome2015.09.0091
Keywords: Bicolor L. Moench; Quantitative Trait Loci; Sugar-Related Traits; Seed; Size; Stay-Green